Structure evolution mechanism of highly ordered graphite during carbonization of cellulose nanocrystals. (September 2019) - Eom, Youngho; Son, Sung Min; Kim, Yea Eun; Lee, Jung-Eun; Hwang, Sang-Ha; Chae, Han Gi
Abstract: The microstructural evolution of highly ordered graphite during high temperature carbonization of cellulose nanocrystals (CNC) was traced in the temperature range of 1000–2500 °C. It was interesting to note that the direct carbonization of CNC under inert environment led to an irregular morphology due to molecular fusion whereas oxidative stabilization at 250 °C under air and subsequent carbonization preserved the pristine needle-like structure of the CNC during carbonization. Various characterizations such as high resolution transmission electron microscopy (HRTEM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS) exhibited that the carbonization of CNC undergoes three distinctive stages of structural changes depending on carbonization temperature: (1) formation of turbo-stratic graphitic structure below 1500 °C (1st stage), (2) phase conversion to polycrystalline graphite between 1500 and 2000 °C (2nd stage), and (3) in-plane homogenization to highly ordered graphite above 2000 °C (3rd stage). Graphical abstract: Image 100